Encyclopedia of Intensive Care Medicine - Vincent, Jean-Louis; Hall, Jesse B. (Springer Berlin Heidelberg : Imprint: Springer, 2012)
The aim of this comprehensive encyclopedia is to provide detailed information on intensive care medicine contributing to the broad field of emergency medicine. The wide range of entries in the Encyclopedia of Intensive Care Medicine are written by leading experts in the field. They will provide basic and clinical scientists in academia, practice, as well as industry with valuable information about the field of intensive care medicine, but also people in related fields, students and teachers will benefit from the important and relevant information on the most recent developments in emergency medicine. The Encyclopedia will contain 4 volumes, and published simultaneously online. The entire field has been divided into 14 sections. All entries will be arranged in alphabetical order with extensive cross-referencing between them.